2021
DOI: 10.3390/ma14051199
|View full text |Cite
|
Sign up to set email alerts
|

Prediction Models Based on Regression and Artificial Neural Network for Moduli of Layers Constituted by Open-Graded Aggregates

Abstract: The impermeable cover in urban area has been growing due to rapid urbanization, which prevents stormwater from being naturally infiltrated into the ground. There is a higher chance of flooding in urban area covered with conventional concretes and asphalts. The permeable pavement is one of Low-Impact Development (LID) technologies that can reduce surface runoff and water pollution by allowing stormwater into pavement systems. Unlike traditional pavements, permeable pavement bases employ open-graded aggregates (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…ANNs can be used wherever simple mathematical models are not applicable due to the complexity of the systems under consideration. This tool has also been widely used in stormwater management studies [59,60]. Multilayer perception (MLP) networks [58] were used in this research.…”
Section: Evaluation Of the Influence Of Catchment Parameters On The R...mentioning
confidence: 99%
“…ANNs can be used wherever simple mathematical models are not applicable due to the complexity of the systems under consideration. This tool has also been widely used in stormwater management studies [59,60]. Multilayer perception (MLP) networks [58] were used in this research.…”
Section: Evaluation Of the Influence Of Catchment Parameters On The R...mentioning
confidence: 99%
“…One of the promises of a digital twin in crop management is for the automatic prediction system to support in deciding the appropriate fertilization period [22][23][24]. Deploying the sensors which monitor the concentration of nutrients present in soil, humidity, and temperature in the real fields to make consistent quality checks.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another study used regression methods and found that random forest regression algorithms provided the highest accuracy for estimating rice shoot dry matter, leaf area index, and nitrogen accumulation [11]. A third study evaluated different approaches for estimating rice aboveground biomass, plant nitrogen uptake, and nitrogen nutrition index, with the random forest algorithm demonstrating superior performance [12]. An additional study focused on using machine learning for early detection of nutrient deficiency in rice through leaf image processing, achieving high testing accuracy and roc_auc score [4].…”
Section: Literature Reviewmentioning
confidence: 99%